Evolusi Komunikasi Budaya Studi tentang Teknologi Digital sebagai Jembatan Tradisi dan Modernitas - Murbinami, Raswitha; Fitria Ayuningtyas; Witanti Prihatiningsih (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This research aims to analyze the role of digital technology in the preservation, promotion, and protection of Traditional Cultural Expressions (TCE) as an effort to bridge tradition and modernity. Digital transformation, particularly through the internet and social media, has changed the way people access, distribute, and appreciate traditional cultural expressions. This research uses a qualitative approach with a critical paradigm through literature review and analysis of international policy documents from WIPO, UNESCO, and related institutions published between 2020 and 2025. Data analysis was conducted using content analysis and critical interpretation techniques based on theories of the political economy of media and cultural commodification. The results show that digital technology plays a dual role: as an effective means of expanding the distribution and increasing the visibility of TCE, while also posing risks to the authenticity, communal ownership, and legal protection of indigenous peoples. Innovations such as Creative Commons licenses, indigenous protocols, and digital rights management have been shown to offer more adaptive protection alternatives. This research concludes that the successful preservation of TCE in the digital age depends on collaboration between indigenous peoples, states, and global institutions in creating an inclusive, ethical, and sustainable digital ecosystem. Keywords: Digital Communication, Cultural Digitalization, Indigenous Communities, Intellectual Property Protection, Traditional Cultural Expressions (TCE).